The streak : how Joe DiMaggio became America's hero - Rosenstock, Barb (Calkins Creek, an imprint of Highlights, 2014)
Chronicles the story of the legendary baseball star, his favorite bat, Betsy Ann, and the longest hitting streak in baseball history, which united the country on the brink of World War II.